Constructing sensitive luminescent thermometers via energy transfer in Ce3+ and Eu2+ co-doped Ca8Mg3Al2Si7O28 phosphors. (28th June 2021) - Zhou, Rongfu; Lin, Litian; Zhao, Hongting; Deng, Tingting; Li, Jingwei
Abstract : Ca8 Mg3 Al2 Si7 O28 :Ce 3+, Eu 2+ phosphors with a melilite structure are designed and prepared for applications in optical thermometry. Their emission colours are tunable due to the energy transfer and thermal quenching of Ce 3+ and Eu 2+ . Abstract : In this study, Ce 3+ and Eu 2+ co-doped Ca8 Mg3 Al2 Si7 O28 phosphors are designed and synthesized for applications in highly sensitive optical thermometry. The host structure is determined by Rietveld refinement based on powder X-ray diffraction (P-XRD) data. The site-dependent luminescence of Ce 3+ and Eu 2+ is discussed on the basis of the Ca8 Mg3 Al2 Si7 O28 structure and low-temperature VUV-UV spectra. Doublet emission bands of Ce 3+ are located at ∼376 and ∼399 nm, and the emission band of Eu 2+ is located at ∼536 nm. Due to energy transfer and different thermal behaviors of Ce 3+ and Eu 2+ luminescence, the emission color of Ca8 Mg3 Al2 Si7 O28 :Ce 3+, Eu 2+ is tunable with different doping levels and temperatures under excitation at 320 nm. The energy transfer mechanism between Ce 3+ and Eu 2+ is analyzed by the Inokuti–Hirayama model. The ratiometric fluorescence intensity of Eu 2+ to Ce 3+ is applied to denote the variation of temperature, and provides sensitivity to the temperature readout. Series of temperature-dependent measurements indicate that the Ca7.97 Ce0.01 Na0.01 Eu0.01 Mg3 Al2 Si7 O28 phosphor is a promising candidate for optical thermometric applications.